An African Learning Network on Sustainability for the development and diffusion of teaching materials and tools on Design for Sustainability in an open-source and copyleft ethos - Vezzoli, Carlo; Ceschin, Fabrizio; M’Rithaa, Mugendi (CARMA, 2009)
It is a shared opinion that sustainable development requires a system discontinuity, meaning that radical changes in the way we produce and consume are needed. Within this framework there is an emerging understanding that an important contribution to this change can be directly linked to decisions taken in the design phase. For this reason design schools have therefore to be able to provide design students with a broad knowledge and effective Design for Sustainability tools, in order to enable a new generation of designers in playing an active role in reorienting our consumption and production patterns. Under this perspective, there is a pressing need of mechanisms that act at the education level, enabling design educators (and researchers) to share knowledge in this field. Along this direction this paper presents the intermediate results of the Learning Network on Sustainability (LeNS) project, an Asian-European multi-polar network for curricula development on Design for Sustainability focused on (Product-Service) System innovation, financed by the European Commission under the Asia-Links programme2. LeNS is a mechanism to develop and diffuse system design for sustainability in design schools with a transcultural perspective. The main output of the project will be the Open Learning E-Package (OLEP), an open web platform that allows a decentralised and collaborative production and fruition of knowledge produced as learning subsidies. It can be described as a modular e-package of teaching materials (texts, slide shows, audio, video, etc) and tools for designers, that design educators (but also students and professionals as designers, entrepreneurs and interested persons/institutions) worldwide will be able to download (free of charge), modify, remix and reuse (copy left). Apart from the contents, the same LeNS web platform is realised in an open-source and copy left ethos, allowingits download and reconfiguration in relation to specific needs, area of interest and interested partners. Within this perspective one of this hypothesis is about the setting up of an African Learning Network on Sustainability, which, taking in consideration the local needs, interests and opportunities, could represent a significant enabling platform capable to sensitise, support and empower a new generation of African design educators, designers and entrepreneurs to reach design practice throughout an open collaborative learning approach.
Keywords: Africa; Learning network; Design for Sustainability (DfS); Didactic materials and tools; Open Learning E-Package